2021
DOI: 10.3389/fonc.2021.679095
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental and Essential Knowledge for Pathologists Engaged in the Research and Practice of Immune Checkpoint Inhibitor-Based Cancer Immunotherapy

Abstract: Extensive research over 100 years has demonstrated that tumors can be eliminated by the autologous immune system. Without doubt, immunotherapy is now a standard treatment along with surgery, chemotherapy, and radiotherapy; however, the field of cancer immunotherapy is continuing to develop. The current challenges for the use of immunotherapy are to enhance its clinical efficacy, reduce side effects, and develop predictive biomarkers. Given that histopathological analysis provides molecular and morphological in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 138 publications
(147 reference statements)
0
6
0
1
Order By: Relevance
“…The patients analyzed in this study were breast cancer cases treated with eribulin at a dose of 1.4 mg/m 2 during a 2-5 min infusion on days Immunohistochemical (IHC) staining using an anti-HLA class I antibody (clone EMR8-5; Hokudo) was performed as described previously. 14,15 Formalin-fixed paraffin-embedded sections of surgical specimens from breast cancer patients (n = 2) were analyzed.…”
Section: Patients Specimens and Immunohistochemical Stainingmentioning
confidence: 99%
“…The patients analyzed in this study were breast cancer cases treated with eribulin at a dose of 1.4 mg/m 2 during a 2-5 min infusion on days Immunohistochemical (IHC) staining using an anti-HLA class I antibody (clone EMR8-5; Hokudo) was performed as described previously. 14,15 Formalin-fixed paraffin-embedded sections of surgical specimens from breast cancer patients (n = 2) were analyzed.…”
Section: Patients Specimens and Immunohistochemical Stainingmentioning
confidence: 99%
“…Cancer immunotherapy provides a completely different therapeutic modality compared with existing treatments for certain types of advanced malignancies for which no effective treatment is available, and may even confer complete remission. 1 Therefore, it is fair to state that cancer immunotherapy has solidified its position as a standard of care, comparable to surgery, radiotherapy, and chemotherapy. Presently, most cancer immunotherapies employ immune checkpoint inhibitors (ICIs) targeting cytotoxic T-lymphocyte-associated protein 4 and/or programmed cell death protein 1/programmed death-ligand 1.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between programmed death‐1 (PD‐1) on T cells and programmed death‐ligand 1 (PD‐L1) on malignant cells, the so‐called effector phase, plays a crucial role in the immune escape of cancer cells, as shown by the clinical efficacy of blocking PD‐1/PD‐L1 in current cancer immunotherapy 11 . PD‐L1 expression is not solely dependent on activated cytotoxic T lymphocyte (CTL)‐derived interferon gamma (IFNγ) but is also regulated by numerous factors 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between programmed death‐1 (PD‐1) on T cells and programmed death‐ligand 1 (PD‐L1) on malignant cells, the so‐called effector phase, plays a crucial role in the immune escape of cancer cells, as shown by the clinical efficacy of blocking PD‐1/PD‐L1 in current cancer immunotherapy. 11 PD‐L1 expression is not solely dependent on activated cytotoxic T lymphocyte (CTL)‐derived interferon gamma (IFNγ) but is also regulated by numerous factors. 12 Accumulating evidence has shown that non‐IFNγ stimulation, including chemotherapeutic agents, induces PD‐L1 expression on malignant cells, although the mechanism and its significance in the cancer microenvironment have not been clarified fully.…”
Section: Introductionmentioning
confidence: 99%